1998
DOI: 10.1056/nejm199804023381401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reperfusion on Biventricular Function and Survival after Right Ventricular Infarction

Abstract: In patients with right ventricular infarction, complete reperfusion of the right coronary artery by angioplasty results in the dramatic recovery of right ventricular performance and an excellent clinical outcome. In contrast, unsuccessful reperfusion is associated with impaired recovery of right ventricular function, persistent hemodynamic compromise, and a high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
120
0
11

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(137 citation statements)
references
References 39 publications
6
120
0
11
Order By: Relevance
“…These studies have also provided information about more effective treatment, with the intention of providing better prognosis for these patients. 8,[21][22][23][24] The present study has demonstrated that 21% of the patients with LV myocardial infarction presented this in association with RV infarction. This is in accordance with the data in the literature, with reported percentages ranging from 14% to 84%.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…These studies have also provided information about more effective treatment, with the intention of providing better prognosis for these patients. 8,[21][22][23][24] The present study has demonstrated that 21% of the patients with LV myocardial infarction presented this in association with RV infarction. This is in accordance with the data in the literature, with reported percentages ranging from 14% to 84%.…”
Section: Discussionmentioning
confidence: 79%
“…Considering similar data, Bowers et al 8 suggested that successful reperfusion by means of primary angioplasty could achieve dramatic improvements in RV performance and improved clinical outcomes among patients with RV myocardial involvement. Furthermore, Mehta et al 29 observed that the presence of RV myocardial involvement itself, rather than the extensive LV infarction, is related to increased risk of death, shock and arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations